Iron Ores and Iron Oxide Materials - Shatokha, Volodymyr (IntechOpen, 2018)
This book provides the multidisciplinary reading audience with a comprehensive state-of-the-art overview of research and innovations in the relationship between iron ores and iron ore materials. The book covers industrial sectors dealing with exploration and processing of iron ores as well as with advanced applications for iron ore materials and therefore entails a wide range of research fields including geology, exploration, beneficiation, agglomeration, reduction, smelting, and so on, thus encouraging life cycle thinking across the entire production chain. Iron remains the basis of modern civilization, and our sustainable future deeply depends upon our ability to satisfy the growing demand for iron and steel while decoupling hazardous emissions from economic growth. Therefore, environmental sustainability aspects are also broadly addressed. In response to socioeconomic and climatic challenges, the iron ore sector faces, this book delivers a vision for the new opportunities linked to deployment of the best available, innovative and breakthrough technologies as well as to advanced material applications.